2016
DOI: 10.1590/1807-1929/agriambi.v20n5p441-446
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and grain yield of upland rice as affected by water deficit

Abstract: A B S T R A C TTo achieve an accurate phenotyping for drought tolerance, it is important to control water stress levels and timing. This study aimed to determine water use by upland rice plants during periods of irrigation withholding and its relationship with grain yield in order to increase the efficiency of this phenotyping. Two experiments were carried out in a randomized block design in which six water treatments (irrigation withholding for periods of 2, 4, 6, 8, 10 and 12 days) were compared, with four r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
4
7
0
1
Order By: Relevance
“…grain length in cross II and grain shape in both crosses exhibited highly significant negative heterosis as a deviation from midparents under both water deficit and normal conditions. Similar results were reported earlier by Abd El-Lattef et al (2008), Ganapathy and Ganesh (2008), Abd-Allah (2009), Hassan et al (2011), Mall et al (2011), Concepcion et al (2015 and Guimaraes et al (2016).…”
Section: -Estimates Of Heterosis and Degree Of Dominancesupporting
confidence: 91%
See 2 more Smart Citations
“…grain length in cross II and grain shape in both crosses exhibited highly significant negative heterosis as a deviation from midparents under both water deficit and normal conditions. Similar results were reported earlier by Abd El-Lattef et al (2008), Ganapathy and Ganesh (2008), Abd-Allah (2009), Hassan et al (2011), Mall et al (2011), Concepcion et al (2015 and Guimaraes et al (2016).…”
Section: -Estimates Of Heterosis and Degree Of Dominancesupporting
confidence: 91%
“…Additive gene effects can be exploited in early generations because the dominance effects were also non-significant and lower in magnitude than these additive effects. Similar results were reported by Shehata et al (2004), Manickavelu et al (2006), Kumar et al (2006, Hassan et al (2011), Hijam et al (2012, Ravikumar et al (2014) and Guimaraes et al (2016).…”
Section: -Estimates Of Genetic Components Of Generation Meansupporting
confidence: 85%
See 1 more Smart Citation
“…,Abd-Allah (2009),Hassan et al (2011),Mall et al (2011),Concepcion et al (2015) andGuimaraes et al (2016).…”
mentioning
confidence: 99%
“…Therefore, the Douradão cultivar showed lower transpiration in well-watered conditions and under moderate water deficit and did not differ from the BRS Soberana in severe water regimes. Guimarães et al (2016b) also found that rice transpiration decreased with water deficit and Cabuslay et al (2002) observed that rice cultivars with moderate tolerance to water stress showed higher relative transpiration rates, which confirms the greater tolerance of the Douradão cultivar to water stress in relation to the BRS Soberana.…”
Section: Resultsmentioning
confidence: 71%